2021
DOI: 10.3390/app11209630
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Commercial Screed Mortar with Low OPC Content by Incorporation of Biomass Fly Ash

Abstract: Substitute Ordinary Portland Cement (OPC) by biomass fly ash (BFA) reduce the environmental impact produced by cement-based materials, and at the same time, decreased the economic and environmental burden associated with the landfilling of this waste. This study aims to evaluate the recycling of BFA as supplementary cementitious materials (SCMs) in a commercial screed mortar formulation. Two BFA varieties, both resulting from fluidized bed combustion of forest residues, were used to replace 17, 50, and 67 wt.%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…The XRD pattern of the BFA samples shows that α-quartz (α-SiO 2 ), calcite (CaCO 3 ), microcline (KAlSi 3 O 8 ), and muscovite (KAl 2 (AlSi 3 O 10 )(OH) 2 ) are the main crystalline detected phases. These findings are in line with the results obtained in XRF and with the crystalline phases reported in the literature (quartz and calcite) [ 4 , 13 , 14 , 15 ]. When qualitatively comparing the BFA1 and BFA2 diffractograms with those of the sieved fractions (BFA1_S and BFA2_S), it is possible to observe that the peaks referring to α-quartz decrease in intensity.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The XRD pattern of the BFA samples shows that α-quartz (α-SiO 2 ), calcite (CaCO 3 ), microcline (KAlSi 3 O 8 ), and muscovite (KAl 2 (AlSi 3 O 10 )(OH) 2 ) are the main crystalline detected phases. These findings are in line with the results obtained in XRF and with the crystalline phases reported in the literature (quartz and calcite) [ 4 , 13 , 14 , 15 ]. When qualitatively comparing the BFA1 and BFA2 diffractograms with those of the sieved fractions (BFA1_S and BFA2_S), it is possible to observe that the peaks referring to α-quartz decrease in intensity.…”
Section: Resultssupporting
confidence: 93%
“…Their surface is generally rough and not strongly vitreous. These morphology features fit the descriptions made by other authors [ 4 , 15 , 16 , 17 ].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In the literature, investigations with biomass fly ashes are scarce. However, recently, Capela et al (2021) [ 9 ], studied the use of FA biomass as a partial substitute for OPC (0 to 67 wt.%) and studied the influence of pretreatments on the properties of the prepared mortars. The authors demonstrated that the replacement of 17 wt.% of OPC by as received FA does not affect the properties of the specimens, which resisted up to 25 freeze–thaw cycles.…”
Section: Introductionmentioning
confidence: 99%